Temporary Agency Work and Firm Performance: Evidence from German Establishment-Level Panel Data - Michael Beckmann; Dieter Kuhn (University of Basel, Center of Business and Economics (WWZ), 2009)
This paper empirically examines the impact of temporary agency work on firm performance using panel data from German establishments. Thereby, special attention is devoted to the question, whether there are performance differences between firms using temporary agency workers (TAWs) as a buffer stock (flexibility strategy) and firms using TAWs for screening purposes (screening strategy). While the theoretical discussion on this issue does not lead to clear-cut results, our empirical investigation provides the following results. First, we find an inverse U-shaped relationship between the share of TAWs and firm performance. Second, we obtain that firms following the screening strategy are significantly more productive than firms following the flexibility strategy. These results are found to be valid in both cross-sectional and panel data settings, so they are robust to unobserved firm heterogeneity.
Keywords: C23; J24; J42; J82; M55; 330; Temporary agency work; firm performance; flexibility strategy; screening strategy; Leiharbeit; Unternehmenserfolg; Humankapital; Arbeitsmarktsegmentation; Schweiz; Deutschland